Thermoelastic damping in FGM nano-electromechanical system in axial vibration based on Eringen nonlocal theory - Rahimi, Z.; Rashahmadi, S. (Прикладная механика, 2017)
The thermo-elastic damping is a dominant source of internal damping in microelectromechanical systems (MEMS) and nano-electromechanical systems (NEMS). The internal damping cannot neither be controlled nor minimized unless either mechanical or geometrical properties are changed. Therefore, a novel FGMNEM system with a controllable thermo-elastic damping of axial vibration based on Eringen nonlocal theory is considered. The effects of different parameter like the gradient index, nonlocal parameter, length of nanobeam and ambient temperature on the thermo-elastic damping quality factor are presented. It is shown that the thermo-elastic damping can be controlled by changing different parameter. Термопружне демпфування є головним джерелом внутрішнього демпфування в мікроелектромеханічних і наноелектромеханічних системах. Внутрішнє демпфування не може бути ні кероване, ні мінімізоване, поки механічні і геометричні властивості матеріалу не є змінними. Тому розглянуто осьові коливання балки з нового матеріалу – функціонально градієнтного матеріалу з врахуванням наноелектромеханічних явищ – в рамках нелокальної теорії Ерінгена. Розглянуто вплив різних параметрів – показника градієнтості, параметрів нелокальності, довжини нанобалки, температури навколишнього середовища – на коефіцієнт термопружного демпфування. Показано, що термопружне демпфування може бути кероване зміною цих параметрів.